Faktor-Faktor yang Berhubungan dengan Keluhan Muskuloskeletal Disorders Pekerja Pengangkut Barang di Pasar Panorama Kota Bengkulu - Ullya Rahmawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Workers porters are one part of the community that needs attention, because the work processes they carry out carry a lot of risks to their health status, one of which is complaints of musculoskeletal disorders (MSDs). Based on the results of a preliminary survey of 5 Bengkulu City Panorama Market workers porters, it was found that 100% had MSDs complaints. The purpose of this study was to determine the factors related to complaints of musculoskeletal disorders (MSDs) on workers porters at the Panorama Market in Bengkulu City. This study was an observational analytic study using a cross sectional study design. The population of the study was 124 freight carriers. The samples of this study were 124 workers with a total sampling technique. Chi square statistical test results found there is a relationship between work position and complaints MSDs (p = 0,000), there is a relationship of workload with complaints MSDs (p = 0.026), there is a relationship of age with complaints MSDs (p = 0.006), there is a relationship between working period and complaints MSDs (p = 0.001) and there is a relationship between BMI and MSDs complaints (p = 0.044). Suggestions that can be given for further research can add variables measuring environmental factors.